The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.paid.2020.110491
|View full text |Cite
|
Sign up to set email alerts
|

Psychological entitlement predicts noncompliance with the health guidelines of the COVID-19 pandemic

Abstract: In this research, we examined whether psychological entitlement predicted noncompliance with the health guidelines of the COVID-19 pandemic. People higher in psychological entitlement typically try to avoid behaviors that might cause themselves harm, but their high expectations, lack of concern about others, and distrust of authority figures could affect their perceptions of the threat of the coronavirus and their views on the benefits of following the health guidelines. Across three studies ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 45 publications
2
31
1
9
Order By: Relevance
“…Previous studies have found that higher socioeconomic status is associated with lower compliance to preventative measures (Zitek & Schlund, 2020). Our results are mixed but indicate that subjective socioeconomic status does not reliably associate with mask wearing.…”
Section: Discussioncontrasting
confidence: 85%
“…Previous studies have found that higher socioeconomic status is associated with lower compliance to preventative measures (Zitek & Schlund, 2020). Our results are mixed but indicate that subjective socioeconomic status does not reliably associate with mask wearing.…”
Section: Discussioncontrasting
confidence: 85%
“…The online learning platform availability is found to be the most important factor resulting in the satisfaction of students. Zitek and Schlund ( 2021 ) suggested that the perceived impact of COVID-19 on daily life is associated with greater health anxiety. Baber ( 2021 ) found the moderating effect of perception about maintaining social distance reduces the effect of social interaction on the effectiveness of online learning during the COVID-19.…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…Moreover, Zitek and Schlund [ 23 ] studied the psychological entitlement in the United States and revealed that the individuals were not concerned about transmitting the disease to others. Therefore, they were less likely to follow the COVID-19 prevention guidelines.…”
Section: Introductionmentioning
confidence: 99%